Algunos apuntes prácticos sobre derecho de seguros en el Perú - Primera entrega - Corzo de la Colina, Rafael (2023)
In this article, the authors attempt to provide a practical review of insurance law in Peru. For that purpose, they use the experience gathered in their years working in this area and allow themselves to go deeper and give their opinion on premiums, the ‘big risks’, the capacity of the companies of the Insurance System to post bonds, among others.The authors intend this text to serve as a practical guide for those involved in insurance law.